2022
DOI: 10.1007/s43538-022-00099-w
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral perspectives of economically important Indian medicinal plants and spices

Abstract: Human respiratory diseases caused by viral infections leads to morbidity. Among infectious diseases, viral infections associated with the respiratory tract remain the primary reason for global deaths due to their transmissibility. Since immemorial, traditional Indian medicinal plants, their extracts, and several phytochemicals can treat various diseases. Sources for this review paper are data derived from a peer-reviewed journal that emphasizes the economic importance of medicinal plants. Several plant-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 173 publications
0
1
0
Order By: Relevance
“…Nutrients regulate the quality as well as magnitude of immune response against viruses (Alam et al, 2021; Wilhelm et al, 2021). The traditional knowledge about use of food items for medicament of immune disorders and air‐borne respiratory tract infections is well documented in Ayurvedic texts (Caraka., 1890; Horváth & Ács, 2015; Pebam et al, 2022). We have systematically reviewed the studies which have identified biologically active chemicals present in the culinary spices and food supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients regulate the quality as well as magnitude of immune response against viruses (Alam et al, 2021; Wilhelm et al, 2021). The traditional knowledge about use of food items for medicament of immune disorders and air‐borne respiratory tract infections is well documented in Ayurvedic texts (Caraka., 1890; Horváth & Ács, 2015; Pebam et al, 2022). We have systematically reviewed the studies which have identified biologically active chemicals present in the culinary spices and food supplements.…”
Section: Introductionmentioning
confidence: 99%